Piggins - Yolen, Jane.; Dyer, Jane (San Diego Harcourt Brace Jovanovich, 1987)
During a dinner party, the lights go out and Mrs. Reynard's beautiful diamond necklace is stolen, but Piggins the butler quickly discovers the real thief.
AD 450
Adult 450
Accelerated Reader AR
Keywords: Pigs -- Fiction; Animals -- Fiction; Mystery and detective stories